SCREENING OF THERMOPHYLIC MICROORGANISM FROM IJEN CRATER BANYUWANGI AS PHYTASE ENZYME PRODUCER - Aline Puspita Kusumadjaja; Tutuk Budiati; Ni Nyoman Tri Puspaningsih; Sajidan Sajidan (Universitas Gadjah Mada, 2009)
Phytase is enzyme which hydrolysis phytic acid to anorganic phosphate and myo-inositol pentakis-, tetrakis-, tris-, bis-, and monophosphate. The use of phytase in feed industry can overcome environment and nutrition problems which were arisen from unmetabolism phytic acid or its salt by poultry, swine and fish. The feed industry needs a thermostable enzyme due to the need of high temperature in pelleting process, i.e. 81 °C. By using thermostabile phytase, the pelleting process will not affect the enzyme activity. Thermostabile phytase can be isolated from microorganism live in hot spring water or volcano crater. In this study, the screening of thermophylic microorganism having thermostabile phytase activity in Ijen Crater, Banyuwangi, has been done. From this process, it was obtained 33 isolates that produce phytase enzyme. Isolate was code by AP-17 yields highest phytase activity, that is 0.0296 U/mL, so this isolate was choosen for further study. The activity of crude phytase enzyme was measured based on the amount of anorganic phosphate that was produced in enzymatic reaction using UV-VIS spectrophotometer at 392 nm. Based on morphology test to identify the gram type of microorganism, isolate AP-17 has a bacill cell type and identified as positive gram bacteria. This isolate was assumed as Bacillus type.